Use of tyrosine kinase inhibitors during pregnancy for oncogenic-driven advanced non-small cell lung carcinoma. (November 2021) - Boudy, Anne-Sophie; Grausz, Noémie; Selleret, Lise; Gligorov, Joseph; Thomassin-Naggara, Isabelle; Touboul, Cyril; Daraï, Emile; Cadranel, Jacques
Highlights: Lung cancer during pregnancy is a rare event but its incidence is on the increase. TKIs should be proposed during pregnancy for oncogenic-driven advanced NSCLC. The maternal benefits should be weighed against fetal risks. Abstract: Introduction: Lung cancer associated with pregnancy is rare but on the increase. The use of tyrosine kinase inhibitor (TKI) therapy for advanced oncogenic-driven non-small cell lung carcinoma (NSCLC) has improved overall survival. Oncological and obstetric outcomes of patients diagnosed with NSCLC and treated by TKIs during pregnancy have been poorly evaluated. Methods: Three cases of NSCLC treated by TKIs during pregnancy were collected from the prospective database of the Cancer Associé à La Grossesse (CALG) network (France) in addition to eight cases identified by a systematic review performed between 2000 and 2021. Results: Among the eleven reported patients, six received an EGFR- and five an ALK-TKI. All patients were young nonsmokers and four had brain metastases at diagnosis. TKI treatment was initiated during the first trimester for three patients. Premature delivery was induced in 10/11 patients. Anamnios occurred in one patient treated by osimertinib and trastuzumab. Five newborns were hypotrophic. No newborn malformations were observed. Diffusion of the TKIs, confirmed by blood cord sampling, represented about 1/3 (EGFR-TKI) and 1/8 (ALK-TKI) of the maternal concentration. No developmental abnormalities were observed in the children (follow-up 30 months). The anti-tumor efficacy and tolerance of TKIs, when reported, appears similar to that described in the general population. Conclusions: Our results support the rationale for using TKIs during pregnancy, both in terms of maternal NSCLC disease control and the relatively mild effects on the fetus. Our data will serve to better inform patients about the risks associated with TKIs used during pregnancy, contributing to shared decision making.